Analisis Hubungan Petugas Apotek Terhadap Pelayanan Informasi Obat Kontrasepsi Oral - Marvel Marvel (UIN Syarif Hidayatullah Jakarta, 2022)
The successful implementation of the Family Planning (Keluarga Berencana) program assists the government in developing reproductive health. The acceptors' knowledge about oral contraceptive drugs may be influenced by drug information conveyed by pharmacy staff, namely pharmacists and their assistants. Therefore, this study aimed to measure relationship between pharmacy staff and information services for oral contraceptives at the South Tangerang Regional Pharmacy using a cross-sectional design. This study used trained simulated patients. The samples surveyed were 152 pharmacies with 132 pharmaceutical technical personnel, and 20 pharmacists as respondent. In terms of drug information services, this study found 94 subjects in the poor category (value of 69.9%), 44 subjects (26.4%) in the moderate category (value between 70-79.9%), and 14 subjects (7.9%) in the good category (value of 80%). There was a significant relationship between the pharmacy staff variable with the total value of drug information services (Pelayanan Informasi Obat) variable (p = 0.016). The result showed that pharmacists provide information services for oral contraceptives better than pharmacy technicians.